Boost Supply Chain with SAP Transportation Management and Logistics Business Network (BN4L) - Karthik, Joseph Sai (Journal of Global Economy, Business and Finance, 2025)
Supply chain networks are increasingly complex due to evolving customer demands and geopolitical uncertainties. The integration of SAP Transportation Management SAP TM and Business Network for Logistics BN4L can significantly enhance logistics operations. This paper explores the integration of SAP TM with BN4L, highlighting their benefits, integration strategies, and overall impact on supply chain efficiency. It aims to provide insights for industry practitioners and researchers on leveraging BN4L addons like Project 44 for improved supply chain visibility and predictive analytics. Key research questions addressed include the impact on different industries, challenges and opportunities, effective use of predictive analytics, and return on investment ROI of the integration. In this paper, we will explore the following research questions: 1) How does the integration of SAP TM and BN4L impact different supply chain industries (e. g., retail, transportation)? 2) What are the key challenges and opportunities associated with implementing and maintaining the integration? 3) How can predictive analytics be effectively leveraged within the SAP TM and BN4L framework to improve decision - making? 4) What is the return on investment (ROI) of integrating SAP TM and BN4L? By addressing these questions, this paper aims to provide a comprehensive understanding of the transformative potential of SAP TM and BN4L integration.